The Effect Of Promotion And Customer Reviews On Purchase Decisions At The Viondy1 Online Shop In West Jakarta City - Yuliah, Dedeh; Nani, Nani (Kompartemen: Kumpulan Orientasi Pasar Konsumen, 2024)
This study aims to determine the effect of promotion and customer reviews on purchasing decisions at the Viondy1 Online Shop in West Jakarta City. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study show that promotion has a significant effect on purchasing decisions, as evidenced by the hypothesis test obtained sig.